International shocks and growth in emerging markets - Poshakwale, Sunil S.; Ganguly, Gaurav (Elsevier, 2015)
The paper provides evidence on the extent and channels of transmission of international shocks on the economic growth of emerging markets. Using a block dynamic factor model, the shocks are decomposed into four components; a general global component, an activity based component, a financial component and a commodity price component. Using a sample of 75 emerging markets over the period 1992–2009, the paper finds that the average effect of international shocks on emerging markets' growth over the entire sample period is negligible, which supports the classic view of isolated, de-coupled emerging markets. However, there is considerable variation both over time, over cross-section and across factors. When we split our sample by time period, we find greater effect of the international factors on the emerging markets' growth during 2002–2009 period. There is evidence which suggests that sensitivity to international shocks has increased over time and at the country level these sensitivities are more pronounced. Although the drivers of integration vary as does the sensitivity to alternative sources of shocks, we find that certain emerging markets have become considerably more integrated with the global economy than others. Overall, there is evidence of a significant impact on the economic growth of some emerging markets of the international shock caused by the global financial crisis.
Keywords: Economic growth; Emerging markets; Factor models; GDP growth; Globalisation